2021
DOI: 10.1177/2399808321994575
|View full text |Cite
|
Sign up to set email alerts
|

Planning for tourist urban evacuation routes: A framework for improving the data collection and evacuation processes

Abstract: Tourism is one of the largest growing industries worldwide. As the number of tourists is rapidly increasing, so too are tourist safety concerns. The increasing frequency of natural disasters along with the growth of urban areas makes it even more complex to address the resilience of tourists during such events. This article proposes a framework for collecting information about tourist locations and flows within urban areas and how to use this information for more efficient and safe evacuation routing. We defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…In the case of a major emergency, evacuation efficiency is most important, and thus, the decision-maker should consider transporting the stakeholders from the danger area to the refuge within the shortest time 13 . However, in some cases, the situation is not an emergency or can be predicted and planned in advance 14 . For tourist evacuation existing studies on tourist evacuation focus on evacuation efficiency, such as accessibility and connectivity.…”
Section: Related Workmentioning
confidence: 99%
“…In the case of a major emergency, evacuation efficiency is most important, and thus, the decision-maker should consider transporting the stakeholders from the danger area to the refuge within the shortest time 13 . However, in some cases, the situation is not an emergency or can be predicted and planned in advance 14 . For tourist evacuation existing studies on tourist evacuation focus on evacuation efficiency, such as accessibility and connectivity.…”
Section: Related Workmentioning
confidence: 99%
“…However, there is still an ongoing debate on how the resilience of infrastructures should be improved. Several researchers have provided solutions (Wachtel et al , 2021; Kumar et al , 2021) to enhance the resilience of infrastructures to withstand disruptive events. Twumasi-Boakye and Sobanjo (2019) concluded that for engineering problems, it is preferable to use resilient-based approaches to prioritise actions to improve the infrastructure’s resilience.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is still an ongoing debate on how the resilience of infrastructures should be improved. Several researchers have provided solutions [10,12] to enhance the resilience of infrastructures to withstand disruptive events.…”
Section: Introductionmentioning
confidence: 99%